Molecular regulation of chronic stress responses in European sea bass, Dicentrarchus labrax - Samaras, Athanasios; Kollias, Spyridon; Pavlidis, Michail (Frontiers in Endocrinology, 2025)
IntroductionThis study examines the effects of predictable repeated chronic stress on the stress response and cortisol metabolism in European sea bass.MethodsFish were exposed to daily stress for 11 days and sampled the next day before or after an additional stressor. Chronically stressed fish showed an attenuated acute cortisol response and altered circulating cortisone levels.Results and DiscussionGene expression analyses revealed stress-induced regulatory changes. In the brain, pomc and bdnf mRNA expression was affected by chronic stress, while crf by acute stress. In the head kidney, gr2 was affected by both stress types, whereas gr1 and mr responded only to acute stress. Neither mc2r, encoding the ACTH receptor, nor hsd11b2, responsible for cortisol inactivation, were affected. In the liver, gr2 and hsd11b2 were upregulated under chronic stress, suggesting an adaptive mechanism to regulate cortisol metabolism. In contrast, gill receptor expression remained largely unchanged, except for acute stress-induced gr2, gr1, and mr downregulation in chronically stressed fish, potentially modulating cortisol signaling. These findings suggest that chronic stress alters neuroendocrine regulation, desensitizing the HPI axis and impairing the acute stress response. Understanding these mechanisms provides insights into chronic stress adaptation in fish, with implications for aquaculture and stress physiology research.